The impact of CKM and customer satisfaction on customer loyalty in Saudi banking sector: The mediating role of customer trust - Abbas N. Albarq (Administrative Sciences, 2023)
This study aims to explore the role of customer knowledge management (CKM) and satisfaction as antecedents of customer trust, and the mediating function of customer trust in the knowledge-loyalty and satisfaction-loyalty in the Saudi banking sector. This study intends to provide light on the significance of CKM and the ways in which it can support consumer trust, loyalty, and satisfaction. Data came from 600 consumers who responded to an online survey. By using regression analysis and descriptive statistics, seven hypotheses were created and tested. The findings exhibited that customer trust has a major impact on loyalty and that customer trust is positively impacted by CKM and satisfaction. Additionally, trust partially mediates the relationship between knowledge, loyalty, and satisfaction. The study contributes to the literature by examining the factors that influence customer loyalty, CKM engagement, satisfaction, and trust in the context of the Saudi banking industry. These research findings are helpful for managers and strategists in figuring out how to create customer loyalty programs that are a fit for their target market. The study is limited to the Saudi banking sector and may not be generalizable to other industries. Additionally, the study is based on self-reported data from customers, which may not accurately reflect their true opinions and behaviors.
Keywords: 350; customer knowledge management; customer satisfaction; loyalty; Saudi; trust